Odpowiedzi

Najlepsza Odpowiedź!
2009-12-17T17:44:20+01:00
A) (x+5)²-(x+3)(x-3)+56=-30
x² +10x +25 - (x²-9)= -30-56
x²+10x+25-x²+9=-86
10x=-86-25-9
10x = -120 / :10
x= -12

b) -5(x-2)-(2x-3)²+4(x-1)(x+1)=18
-5x+10 - (4x²-12x+9) +4(x² - 1) = 18
-5x+10-4x²+12x - 9 +4x²- 4=18
7x=18-10+9 +4
7x=21 /:7
x= 3

c)(3x-1)²+5(4-x²)-(2x-5)(2x+5)=10
9x² - 6x +1 + 20 - 5x² - 4x² + 25 = 10
-6x=10-25-1-20
-6x=-36 / :-6
x = 6
d)2(x-8)(x+8)-7(x²-2)+5(x-3)²=-9
2(x²- 64) - 7x² + 14+ 5(x² - 6x +9) = -9
2x² - 128 - 7x² +14+5x² -30x+45=-9
-30x=-9+128-14-45
-30= 60/:-16
x= -2
e)2x(x+3)+(x+4)²=(x-1)(3x+2)+3
2x²+6x +x²+8x+16=3x²+2x-3x-2+3
14x+x=1-16
15x=-15 / :15
x=-1